What activities do patients hope to perform following anatomic total shoulder arthroplasty but are unable to? Looking beyond patient-reported outcome measures - Alexander E. White, MD; Nicolas Pascual-Leone, MD; Anthony Finocchiaro, BS; Christopher M. Brusalis, MD; David M. Dines, MD; Joshua S. Dines, MD; Andreas Kontaxis, PhD; Samuel A. Taylor, MD; Lawrence V. Gulotta, MD; Michael C. Fu, MD, MHS (JSES International)
Background: Patients undergoing anatomic total shoulder arthroplasty (aTSA) routinely achieve significant improvements in common patient-reported outcome measures (PROMs). While these structured PROMs produce reliable and standardized data for surgeons, individual patient desires and expectations related to postoperative activities may not be completely captured in standard PROMs. The purpose of the present study was to identify specific activities, sports, and/or hobbies that patients wish they could perform but are unable to following aTSA at a minimum of 2 years postoperatively. Methods: Patients who underwent primary aTSA, with a primary diagnosis of glenohumeral osteoarthritis between February 1, 2016 and January 1, 2021, were identified using an institutional clinical registry. A survey was sent to patients at a minimum of 2 years postoperatively, which included a free-text-response section in addition to 8 selection-based questions assessing patients’ ability to perform various activities. Results: The survey was sent to 601 patients and 395 responded (65.7% response rate). The mean age at the time of the surgery for responders was 65.75 ± 8.8 years. There was no significant difference in age (P = .095), sex (P = .691), race (P = .090), or ethnicity (P = .054) between responders and nonresponders. The majority of patients had no difficulty managing toileting (93.7%), driving a car (92.4%), washing their hair (91.9%), and putting on a seatbelt (90.7%). Of the 395 total responders, 131 (33.2%) patients reported at least one desired activity that they could not perform. Of these 131 patients, weightlifting (14.5%), throwing a ball (12.9%), playing tennis (11.4%), carrying/holding groceries (11.4%), and performing pushups/planks (11.4%) were most commonly reported. Conclusion: Following aTSA, patients are able to perform the majority of activities of daily living without difficulty. A subset of patients desire but are unable to participate in several sports and hobbies following aTSA—most commonly, weightlifting, tennis, throwing a ball, and swimming. These limitations present opportunities for further improvements in postoperative outcomes.